Analisis Persepsi Pasien dalam Memutuskan Pemanfaatan Inden Rawat Inap Kasus Bedah Elektif RSI Jemursari Surabaya - Dini Aftin Rahmadevi (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2018)
RSI Jemursari Surabaya has a queueing system for patients in elective surgical services, but there were some canceled services during the last five months of 2016. Reservation of hospitalization system was implemented to optimize the service, especially for elective surgical cases. This study was conducted to analyze the difference of elective surgical patient’s perception. This is a descriptive-quantitative study with a cross-sectional approach for data collection. Simple random sampling technique was used to determine the sample size. Sample criteria include patients who are 25 to 46 years old and domicile in Surabaya. Data were collected by the questionnaires given to 50 respondents. There were two types of respondents; patients that decided to cancel and not to cancel the service. The statistical test of this study used Sample T-Test with significance value 0.05. The perceptions of waiting time can determine the decision of the patients to take the service. The shorter period of waiting time (≤7 days) would minimize the cancelation probability of elective surgery. This study concluded that there were dissimilarities of patient’s perception in terms of waiting time for elective surgical reservation. Keywords: decision, elective surgery, hospitalize, perceptions, utilization